PERUMUSAN STRATEGI PEMASARAN FRY COUNTER DENGAN PENDEKATAN MODEL AIDA - Oktoriyana, Andi; Sumarwan, Ujang; Hartoyo, Hartoyo (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2014)
This research examined factors which are mentioned in various literatures that have influence on AIDA models to buy fry counter which are attention, interest, and desire. The model also influenced by perceived attributes, personal characteristics, and external factors. Furthermore, the analysis result become a basic for formulating the marketing strategy of fry counter as an innovative product. Analysis was carried out using Structural Equation Modeling. The data for this study were collected from 152 respondents who were fish farmers located in Sukabumi Regency, West Java Province. This research found that external and internal factors influenced positively perceived attributes faktors. The external and perceived attributes factors also influenced positively attention factor. The external factor had negative influence but internal and attention factors had positive influence on consumer’s interest. Perceived attributes and interest factors influenced positively desire factor. Managerial implications is elaborated in the discussion.